Consumer Satisfaction as a Mediator of the Effects of Food Quality and Price on Repurchase Intention at Hisana Fried Chicken in Palu City - Miska Auliyah; Muzakir; Zakiyah Zahara; Farid (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effects of food quality and price on repurchase intention, with consumer satisfaction as a mediating variable, at Hisana Fried Chicken in Palu City. Using a quantitative approach, data were collected through questionnaires from 180 respondents selected by purposive sampling. The data were analyzed using SEM-PLS. The results show that food quality and price have positive and significant effects on consumer satisfaction and repurchase intention. Consumer satisfaction also significantly mediates the effects of food quality and price on repurchase intention. These findings highlight the importance of maintaining food quality and appropriate pricing to encourage repurchase intention. Keywords: Food Quality; Price; Consumer Satisfaction; Repurchase Intention